Outcomes With First-Line PD-1/PD-L1 Inhibitor Monotherapy for Metastatic Renal Cell Carcinoma (mRCC): A Multi-Institutional Cohort - Barata, Pedro; Hatton, Whitley; Desai, Arpita; Koshkin, Vadim; Jaeger, Ellen; Manogue, Charlotte; Cotogno, Patrick; Light, Malcolm; Lewis, Brian; Layton, Jodi; Sartor, Oliver; Basu, Arnab; et al. (Frontiers in Oncology, 2020)
Introduction The treatment landscape of metastatic renal cell carcinoma has advanced significantly with the approval of combination regimens containing an immune checkpoint inhibitor (ICI) for patients with treatment-naïve disease. Little information is available regarding the activity of single agent ICIs for patients with previously untreated mRCC not enrolled in clinical trials. Methods This retrospective, multicenter cohort included consecutive treatment-naïve mRCC patients from six institutions in the USA who received ≥1 dose of an ICI outside a clinical trial, between June 2017 and October 2019. Descriptive statistics were used to analyze outcomes including overall best response rate (ORR), progression-free survival (PFS) and tolerability. Results The final analysis included 27 patients, 70% men, median age 64 years (range 42-92), 67% Caucasian and 33% with ECOG 2 or 3 at baseline. Most patients had intermediate risk (85%, IMDC) with clear cell (56%), papillary (26%), unclassified (11%), chromophobe (4%) and translocation (4%) RCC. All patients had evidence of metastatic disease involving the lungs (59%), lymph node (41%), CNS (19%), liver (11%), adrenal gland (11%) and bone (11%). The median time on ICI was 3.1 (0.1-26.8) months and the median PFS was 6.3 (95% CI, 0-18.6) months. Among the 22 patients with an evaluable response, the best ORR was 36% including two complete responses and six partial responses. The ORR was 32% (n=1 complete response, n=6 partial response) in clear cell and 5% (n=1 complete response) in non-clear cell RCC. Adverse events (AEs) of any cause were reported in 37% and included fatigue (11%), dermatitis (11%), diarrhea (7%) and shortness of breath (7%). Significant AEs (30%) included shortness of breath (7%), acute kidney injury (4%), dermatitis (4%), clostridium difficile infection (4%), cerebrovascular accident (4%) and fatigue (7%). Three patients discontinued therapy due to grade 4 AEs. Conclusions In this multi-institutional case series, single-agent ICI demonstrated objective responses and was well tolerated in a heterogeneous cohort treatment-naïve mRCC cohort. ICI monotherapy is not the standard of care for patients with mRCC and further investigation is necessary to explore predictive biomarkers for optimal treatment selection in this setting.